2014
DOI: 10.1002/jnr.23432
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor‐α inhibitors alleviation of experimentally induced neuropathic pain is associated with modulation of TNF receptor expression

Abstract: Inflammation plays a key role in the development of sensitization after peripheral nerve damage. We recently demonstrated that tumor necrosis factor-α receptor (TNFR) levels in the spinal cord correlate with pain sensation in herniated disc patients in a rat chronic constriction injury (CCI) model. By using the sciatic nerve CCI model, we studied the effect of anti-TNF-α treatment on recovery from hypersensitivity and TNFR expression in the dorsal root ganglion (DRG) and dorsal horn (DH). Experimental groups c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 47 publications
1
24
0
1
Order By: Relevance
“…TNF-a protein has been reported to correspond with decreased pain thresholds [38]. In agreement, it is found that anti-TNF-a treatment resulted in a significant alleviation of pain in a rat CCI model [39], consistently a study showed antimechanical allodynia effect of a compound in rat CCI model, and it was related to decrease in TNF-a expression in the sciatic nerve [40].…”
Section: Discussionmentioning
confidence: 61%
“…TNF-a protein has been reported to correspond with decreased pain thresholds [38]. In agreement, it is found that anti-TNF-a treatment resulted in a significant alleviation of pain in a rat CCI model [39], consistently a study showed antimechanical allodynia effect of a compound in rat CCI model, and it was related to decrease in TNF-a expression in the sciatic nerve [40].…”
Section: Discussionmentioning
confidence: 61%
“…34 TNF and IL-1 have also been shown to modulate pain perception. 35,36 Doong et al demonstrated that variations in pro- and anti-inflammatory genes are associated with pain, fatigue, sleep disturbance, and depression in patients with breast cancer. 5 These inflammatory cytokines are known to be up regulated in CRS.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-α influences neural survival, exerting both neuroprotective and neurodegenerative actions [13]. Following peripheral nerve injury, upregulation of TNF-α expression has been documented in several neuropathic pain models [14]. In contrast, anti-inflammatory cytokines, such as interleukin 4 (IL-4), may inhibit pro-inflammatory cytokine response.…”
Section: Introductionmentioning
confidence: 99%